Ecotoxicological assays applied in soils contaminated by petroleum hydrocarbons - Souza, T. S. [UNESP]; Chistofoletti, C. A. [UNESP]; Fontanetti, C. S. [UNESP] (My University, 2011)
Soil is the final destination of several types of residues of anthropic origin, discharged intentionally or accidentally. The environmental impacts resulted from the petroleum industry in the terrestrial ecosystem are a growing problem. Hydrocarbons of low molecular weight, small aliphatics and BTEX (benzene, toluene, ethylbenzene and xylene) present considerable hydrosolubility. BTEX have great mobility in the soil and can reach easily the water table. Polycyclic aromatic hydrocarbons (PAHs) are formed as by-products or incomplete combustion of organic matter. Several PAHs present genotoxic and carcinogenic properties. In the soil, these compounds and the metabolites resulted from their degradation can affect directly the terrestrial biota and indirectly the aquatic ecosystem by percolation; besides presenting potential to affect negatively the human health. Thus, biological assays (bioassays), which consist in the assessment of the exposure effects of live organisms in contaminated soil, have been required. Bioremediation of soils contaminated with petroleum hydrocarbons is an indispensable alternative for the recovery of the quality of the terrestrial ecosystem, through the removal or reduction, complete or partial, of the concentration of these compounds. In this process, microorganisms use the organic compounds present as substrate for the growth and energy generation and convert them into CO2, H2O and biomass. However, it has been documented that the reduction in the concentration of hydrocarbons is not always followed by decrease in the toxicity of the soil; incomplete degradation and the formation of intermediary metabolites may lead to an increase of the toxicity. Due to the complexity of the bioremediation of soils contaminated with petroleum residues, bioassays are indispensable in the evaluation of the success of this process. In this context, it is here presented a review of the principal ecotoxicological assays with microorganisms, plants and invertebrates used in the monitoring of soils contaminated with petroleum hydrocarbons and/or bioremediated. In a complementation to conventional chemical tests, biological assays can be used with success to identify soils contaminated with petroleum residues, assess the efficacy of a bioremediation technology and, finally, monitor sites already restored. © 2011 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Bioremediation; Biossays; Genotoxicity; Oil; Soil ecotoxicology